2018
DOI: 10.1007/s10096-018-3270-2
|View full text |Cite|
|
Sign up to set email alerts
|

Occult bacteremia etiology following the introduction of 13-valent pneumococcal conjugate vaccine: a multicenter study in Spain

Abstract: Little is known about occult bacteremia (OB) in Spain following the introduction of the 13-valent pneumococcal conjugated vaccine (PCV13). Our aim was to describe the microbiologic characteristics and management of OB among children aged 3-36 months in Spain in the era of PCV13. Data were obtained from a multicenter registry of positive blood cultures collected at 22 Spanish emergency departments (ED). Positive blood cultures performed on patients aged 3-36 months from 2011 to 2015 were retrospectively identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In a study describing the microbiologic characteristics and management of 67 OB patients diagnosed at 22 PEDs in Spain in the PCV13 era (2011-2015), a total of 47 (70.1%) were managed as outpatients, 18 (38.3%) were prescribed antibiotics at PED, SP was isolated in 79.1% and 42.2% of the isolated serotypes were included in the PCV13. 5 In the present study, we continued a previous report ending in 2014 and showing a significant decrease in PCV7/PCV13 pneumococcal serotypes in the aetiology of OB, accompanied by a parallel increase in non-PCV13 serotype isolation. 2 In the present study, no PCV13 isolates were reported anymore from 2011, and no pneumococcal isolates were reported during 2013-2019.…”
Section: B R I E F R E P O R T Near-elimination Of Occult Bacteraemia...supporting
confidence: 90%
See 1 more Smart Citation
“…In a study describing the microbiologic characteristics and management of 67 OB patients diagnosed at 22 PEDs in Spain in the PCV13 era (2011-2015), a total of 47 (70.1%) were managed as outpatients, 18 (38.3%) were prescribed antibiotics at PED, SP was isolated in 79.1% and 42.2% of the isolated serotypes were included in the PCV13. 5 In the present study, we continued a previous report ending in 2014 and showing a significant decrease in PCV7/PCV13 pneumococcal serotypes in the aetiology of OB, accompanied by a parallel increase in non-PCV13 serotype isolation. 2 In the present study, no PCV13 isolates were reported anymore from 2011, and no pneumococcal isolates were reported during 2013-2019.…”
Section: B R I E F R E P O R T Near-elimination Of Occult Bacteraemia...supporting
confidence: 90%
“…The post‐PCV13 annual incidence rate of OB was 5/100,000 children. In a study describing the microbiologic characteristics and management of 67 OB patients diagnosed at 22 PEDs in Spain in the PCV13 era (2011–2015), a total of 47 (70.1%) were managed as outpatients, 18 (38.3%) were prescribed antibiotics at PED, SP was isolated in 79.1% and 42.2% of the isolated serotypes were included in the PCV13 5 …”
Section: Figurementioning
confidence: 99%
“…We extracted demographic data, medical history, PCV status (type and number of doses received), previous antibiotic use, fever characteristics (maximum temperature and the presence of fever in the PED), laboratory test values, management during the index visit at the PED, PED discharge diagnoses, follow-up visit site, diagnosis and disposition at follow-up visit; results of further workup (where relevant), such as repeat BC, complete blood count, chest radiograph, spinal fluid assessment, urinalysis, and urine culture; and antibiotic administration or prescription. 18,19…”
Section: Methodsmentioning
confidence: 99%
“…The clinical characteristics of these patients, including age, sex, onset of fever, temperature, and white blood cell counts, were comparable to those of patients in other studies reporting FWS among children aged 3 to 36 months in Asia 12 and Europe. 13-15 One major issue in this study was the immunization status of the enrolled children. We obtained an immunization history for 60 patients (90%); all of them had received only the basic immunizations included in Thailand’s national immunization schedule according to their ages, except the PCV and Hib vaccine.…”
Section: Discussionmentioning
confidence: 99%